HISTORICIZING ISLAM AFTER COMMUNISM: Adeeb Khalid and the Politics of Religion in Central Asia - Nuh, Zulkifli Muhammad; Sofiandi, Sofiandi; Masduki, Moh (Asia-Pacific Journal on Religion and Society, 2025)
This article examines Adeeb Khalid’s Islam after Communism: Religion and Politics in Central Asia as a theoretical contribution to the study of religion and politics, rather than merely a regional account of post-Soviet Islam. Challenging dominant narratives of Islamic revival and radicalization, Khalid emphasizes the importance of historicizing Islam by foregrounding the legacies of Soviet secularism and postsocialist governance. Through a qualitative and interpretive reading of Khalid’s work, this article argues that Islam in Central Asia has been reconfigured as national heritage, bureaucratized through state control, and securitized within authoritarian political frameworks. These processes have reshaped Muslim subjectivities and politicized everyday religious practices from above, driven largely by state anxiety rather than popular mobilization. By highlighting continuity rather than rupture in state–religion relations, the article complicates liberal assumptions about secularization and religious freedom in post-authoritarian contexts. It concludes that Khalid’s insistence on historicity offers a transferable analytical framework for understanding religion in post-imperial and postsocialist societies beyond Central Asia.